Layanan Konseling Kelompok dengan Teknik Modeling Simbolik dalam Meningkatkan Self Efficacy Siswa SMA Negeri 1 Percut Sei Tuan - Rambe, Nurul Zanna; Manurung, Purbatua; Sinaga, Harwansyah Putra (Pusdikra-Publishing.com, 2024)
This research aims to increase students' self-efficacy through group counseling services using symbolic modeling techniques in class XI MATLANSOS SMA Negeri 1 Percut Sei Tuan. The research method used was Counseling Guidance Action Research (PTBK), with research subjects of 8 students selected based on low and medium levels of self-confidence. Data collection techniques include self-efficacy scales, interviews, and observations. Data analysis was carried out descriptively qualitatively using the data analysis model from Miles and Huberman. The research results showed a significant increase in students' self-confidence levels after being given intervention through symbolic modeling technique group counseling services. In cycle I, the percentage increase in student self-confidence reached 63%, and in cycle II, this percentage increased to 100%. This shows that the intervention carried out is effective in increasing students' self-efficacy, so that they become more confident in speaking and actively participating in class.